The Relationship between Perceived Organizational Justice and Organizational Commitment with Job Satisfaction in Employees of Northern Tehran Health Care Center - Mohammad-Hossein Safi; ّFarima Mohamadi; Shahnam Arshi (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Today, the organizations are obligated to take sufficient attention to human resources in order to attain greater efficiency and ultimately achieve their goals. Considering the importance of desirable behavior in organizations and its impact on the attitudes and perceptions of employees, it is necessary to pay special attention to the treatment of staff and their needs. The present study was prepared to investigate the relationship between organizational justice and organizational commitment and job satisfaction among health care employees in north Tehran. Materials and Methods: The study was done descriptive-analytical among employees with at least 6 months of experience and with a sample size of 259 patients at the health center. Data collection tools consisted job satisfaction, organizational justice and organizational commitment questionnaires. SPSS software was used for data analysis and Pearson's correlation coefficient and T-test was used for independent groups and regression. Results: The mean (SD) of Job satisfaction in employees was 50.1 (12.3), perceived organizational justice was 66.4 (1.17) and organizational commitment was 61.3 (5.7), out of 100. The result value of the correlation coefficient indicates positive and significant relationship between organizational justice and organizational commitment with job satisfaction. Also, components of affective commitment and normative commitment has a significant relationship with job satisfaction, and all of the components of organizational justice (distributive justice, procedural justice, interactional justice) have a significant positive correlation with job satisfaction. Regression analysis indicated that organizational justice and organizational commitment are able to predict job satisfaction of the employees. But the components of procedural justice and distributive justice were not able to predict job satisfaction, and job satisfaction can be predicted only through interactional justice. Affective commitment and normative commitment were able to predict job satisfaction as well, and continuous commitment component is not able to predict job satisfaction. Conclusion: According to the correlation of organizational justice and organizational commitment with job satisfaction, managers can use efficient methods such as effective management, freedom of action, motivation and self-care, in-service training, the division of labor based on merit and ability, etc. to increase commitment, job satisfaction and justice perceptions of the employees, affect their behavior and increase their efficiency and effectiveness in order to further the organizational goals.